Strategi dan Manfaat Layanan Open Access Perpustakaan dalam Peningkatan Budaya Literasi - Amin, Afriadi; Batubara, Abdul Karim; Priatmana, Aldi; Tanjung, Siti Pardiani; Nasution, Ineke Maylingrum (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
The library acts as a container for various sources of information. However, as technology advances, libraries must be able to offer open services so that the community and students can make the most of existing resources that can awaken a culture of literacy. This study uses a qualitative approach with a literature study paradigm. The findings show that the concept of an open access-based digital library makes it easier for users to increase literacy culture. Open access digital libraries have the potential to help increase access to and use of information and literature, promote literacy, and help expand knowledge and innovation. The strategies that can be implemented in library open access services to improve literacy culture are: 1) facilitating open access through an easy-to-use online access system. 2) guidance and training for students and the community, 3) Collaboration with schools and universities, 4) Marketing and promotion, 5) Provision of quality resources, 6) Literacy activity programs, such as joint reading events, literacy workshops, and writing competitions.